PENGEMBANGAN E-LKPD BERBASIS MODEL THINK TALK WRITE(TTW) BERBANTUAN APLIKASI LIVEWORKSHEETS UNTUKKEMAMPUAN KOMUNIKASI MATEMATIS - Rindy Yani; Sri Rahmah Dewi Saragih (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
The research aims to develop a valid, practical, and effective Think Talk Write (TTW)-based e-LKPD assisted by the Liveworksheets application to improve students' mathematical communication skills in trigonometry. The research is motivated by students' low mathematical communication skills in conveying mathematical ideas, using symbols and notation appropriately, and presenting mathematical representations in problem solving. This study uses the Research and Development (R&D) method with a 4D development model consisting of the Define, Design, Develop, and Disseminate stages. The research subjects are 33 students at Xth-2 class of SMK SMK Swasta Al-Ma'shum Sidodadi. The research instruments consisted of a validation sheet, a teacher and student response questionnaire, and a mathematical communication skills test. The results showed that the developed e-LKPD met the criteria for validity based on the validator's assessment, practicality based on teacher and student responses, and effectiveness with a classical completion rate of 82%. Thus, the TTW-based e-LKPD assisted by Liveworksheets is suitable for use in mathematics learning to help improve students' mathematical communication skills.